Prevalence and risk factors for intestinal parasitic infections in pregnant women residing in three districts of Bogotá, Colombia - Angela Fernanda Espinosa Aranzales; Katja Radon; Guenter Froeschl; Ángela María Pinzón Rondón; Maria Delius (BMC, 2018)
Abstract Background Intestinal parasitic infections (IPI) lead to significant morbidity and mortality in pediatric and adult populations worldwide. Intestinal parasitism during pregnancy is of interest as it may affect the health of pregnant women and their offspring. This study determined the prevalence of IPI in pregnant women living in substandard conditions in three urban districts of Bogotá, Colombia. Associations between prevalence and sociodemographic factors, housing, and living conditions were also evaluated. Methods In a cross-sectional and community-based study, pregnant women were recruited from three districts of Bogotá. A total of 550 participants answered a questionnaire; 331 of these also provided stool samples, with 233 providing one and 98 providing two stool samples. Questionnaire responses were associated with the presence of intestinal parasites, which was determined using a standard combined microscopy technique including direct wet mount and formol-ether concentration. Results were verified by supplementary examination of 48 stool samples by quantitative polymerase chain reaction (qPCR). Results Among pregnant women who lived in selected poor residential areas in Bogotá, the overall prevalence of intestinal parasitism was 41% with 9% polyparasitism. Pathogenic parasites were present in 1.2% of the 331 participants including Giardia lamblia and Ascaris lumbricoides. Higher prevalence was found for parasites with debated pathogenicity, including Blastocystis hominis (25%), Endolimax nana (15%), Entamoeba coli (8%), and Iodamoeba butschlii (2%). Entamoeba histolytica/dispar complex was also detected (1.5%). When comparing a subset of stool samples using the combined microscopy technique and qPCR, the latter detected a higher 58.3% overall IPI prevalence. Higher prevalence of infections by any intestinal parasite was found in participants who had never been dewormed (p = 0.01). Higher but not statistically significant associations were found between any parasite and women living with a partner, and intestinal polyparasitism and being from a minority group and not having a water sink. Conclusions This first study of the prevalence of intestinal parasitism in Bogotá focused on pregnant women living in poverty, found a high prevalence of intestinal parasites of debated pathogenicity, and confirmed a low prevalence of pathogenic intestinal parasites. These results highlight the need for educational interventions to disrupt transmission routes for prevalent parasites.